Recent Insights into Aeromonas salmonicida and Its Bacteriophages in Aquaculture: A Comprehensive Review - Park, Seon Young; Han, Jee Eun; Kwon, Hyemin; Park, Se Chang; Kim, Ji Hyung (Journal of microbiology and biotechnology, 2020)
The emergence and spread of antimicrobial resistance in pathogenic bacteria of fish and shellfish have caused serious concerns in the aquaculture industry, owing to the potential health risks to humans and animals. Among these bacteria, , which is one of the most important primary pathogens in salmonids, is responsible for significant economic losses in the global aquaculture industry, especially in salmonid farming because of its severe infectivity and acquisition of antimicrobial resistance. Therefore, interest in the use of alternative approaches to prevent and control infections has increased in recent years, and several applications of bacteriophages (phages) have provided promising results. For several decades, and phages infecting this fish pathogen have been thoroughly investigated in various research areas including aquaculture. The general overview of phage usage to control bacterial diseases in aquaculture, including the general advantages of this strategy, has been clearly described in previous reviews. Therefore, this review specifically focuses on providing insights into the phages infecting , from basic research to biotechnological application in aquaculture, as well as recent advances in the study of .